2021
DOI: 10.1186/s12885-021-08831-3
|View full text |Cite
|
Sign up to set email alerts
|

Building a biopsychosocial model of cancer-related fatigue: the BIOCARE FActory cohort study protocol

Abstract: Background Cancer-related fatigue (CRF) is the most common side effect of cancer and cancer treatment. CRF prevalence is up to 50% in breast cancer patients and can continue several years after cancer remission. This persistent subjective sense of exhaustion is multifactorial. Numerous parameters have been evidenced to be related to CRF across biological, physical, psychological, social and/or behavioral dimensions. Although CRF has been studied for many years, the majority of previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Through the analysis of the co-cited reference network, our study identified the following research frontiers in this discipline: the efficacy goals of exercise therapy in the adjuvant treatment of patients after tumor resection ( 43 ), physical behavior and activity levels ( 44 , 45 ), exercise levels ( 45 , 46 ), exercise patterns ( 46 ), exercise sites ( 47 ), treatment regimens ( 48 50 ), and the clinical efficacy and mechanism of exercise therapy in improving sleep therapy and living standards in chemotherapy patients ( 51 ). Typical representative studies suggest: cancer patients should be helped to establish healthy eating behaviors and develop individualized exercise behavior and exercise level intervention strategies ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through the analysis of the co-cited reference network, our study identified the following research frontiers in this discipline: the efficacy goals of exercise therapy in the adjuvant treatment of patients after tumor resection ( 43 ), physical behavior and activity levels ( 44 , 45 ), exercise levels ( 45 , 46 ), exercise patterns ( 46 ), exercise sites ( 47 ), treatment regimens ( 48 50 ), and the clinical efficacy and mechanism of exercise therapy in improving sleep therapy and living standards in chemotherapy patients ( 51 ). Typical representative studies suggest: cancer patients should be helped to establish healthy eating behaviors and develop individualized exercise behavior and exercise level intervention strategies ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%